2006
DOI: 10.1002/rra.920
|View full text |Cite
|
Sign up to set email alerts
|

Creating a disturbance: manipulating slackwaters in a lowland river

Abstract: The dynamic nature of habitat patches in rivers is driven primarily by flow regime. Altered hydrology, through river regulation, can limit the size and distribution of slackwater patches; important areas for the development of young fish and for shrimp in lowland rivers. Between late October 2002 and late January 2003, we investigated responses of fish, shrimp and their potential prey to the experimental creation of slackwaters and, conversely, to the experimental creation of flowing patches, by diverting wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 40 publications
1
47
1
Order By: Relevance
“…Fluvial dynamics create a mosaic of habitats within river-floodplain systems including off-channel habitats such as oxbow lakes, sloughs and other slack water areas (Amoros and Bornette, 2002). These habitats serve a variety of ecological functions including spawning and nursery areas and refuge from high flows in the main channel (Sabo and Kelso, 1991;Humphries et al, 2006;Pease et al, 2006). Physicochemical attributes of different habitat units have a strong influence on local species assemblages (Tejerina-Garro et al, 1998;Winemiller et al, 2000;Suarez et al, 2004) and interactions between flood dynamics and habitat characteristics influence the value of different habitats for spawning, feeding or refuge (Feyrer et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Fluvial dynamics create a mosaic of habitats within river-floodplain systems including off-channel habitats such as oxbow lakes, sloughs and other slack water areas (Amoros and Bornette, 2002). These habitats serve a variety of ecological functions including spawning and nursery areas and refuge from high flows in the main channel (Sabo and Kelso, 1991;Humphries et al, 2006;Pease et al, 2006). Physicochemical attributes of different habitat units have a strong influence on local species assemblages (Tejerina-Garro et al, 1998;Winemiller et al, 2000;Suarez et al, 2004) and interactions between flood dynamics and habitat characteristics influence the value of different habitats for spawning, feeding or refuge (Feyrer et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrodynamic forces often constrain these microinvertebrates, directly or indirectly, by affecting their life history patterns (Rzoska, 1978;Saunders and Lewis, 1989), habitat characteristics (Humphries et al, 2006), dispersal patterns (Speas, 2000), resource acquisition (Guelda et al, 2005) and biotic interactions (Baranyi et al, 2002;Keckeis et al, 2003). As a result, communities occurring in the main channel flow are often of relatively low abundance and/or biomass (Basu and Pick, 1996;Ietswaart et al, 1999), and are typically comprised of small-bodied taxa with short generation times (Shiel et al, 1982;Pace et al, 1992;but still experience some form of mixing or exchange with the main flow (Lancaster and Hildrew, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…[3] Slackwaters have been found to contain significantly greater numbers of fish, shrimp, and zooplankton than midchannel habitats in lowland rivers [Bowen et al, 2003;Richardson et al, 2004;Nielsen and Watson, 2008;Ning et al, 2010] with an order of magnitude more fish and shrimp observed in one study [Humphries et al, 2006]. They have also been found to provide refuge from excessively high-water velocities, which stress many biota [Schiemer et al, 2001;Maddock et al, 2004] enabling recolonization of the channel following flow recession [Lancaster and Belyea, 1997;Speirs and Gurney, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…[40] While slackwaters represent only one key habitat within the complexity of natural rivers [Cooper et al, 1997], they are empirically associated with significantly greater numbers of fish, shrimp, and zooplankton than in fast-flowing waters [Bowen et al, 2003;Richardson et al, 2004;Humphries et al, 2006;Nielsen and Watson, 2008] and physically associated with processes such as organic matter retention [Schiemer et al, 2001]. Therefore, it is probable that changes to slackwaters resulting from regulation are likely to influence biota that use slackwaters at some or multiple stages in their life cycle.…”
Section: Impacts Of Regulation On Slackwatersmentioning
confidence: 99%
See 1 more Smart Citation